Advances in the Neurocognition of Music and Language - Sammler, Daniela; Elmer, Stefan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Neurocomparative music and language research has seen major advances over the past two decades. The goal of this Special Issue on "Advances in the Neurocognition of Music and Language" was to showcase the multiple neural analogies between musical and linguistic information processing, their entwined organization in human perception and cognition, and to infer the applicability of the combined knowledge in pedagogy and therapy. Here, we summarize the main insights provided by the contributions and integrate them into current frameworks of rhythm processing, neuronal entrainment, predictive coding, and cognitive control.